2003
DOI: 10.1080/02643290244000202
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries and Eccentricities in Studies of Lateralised Word Recognition: A Response to Nazir

Abstract: The anatomical arrangement of the human visual system offers considerable scope for investigating functional asymmetries in hemispheric processing. In particular, because each hemisphere receives information initially from the contralateral visual hemifield, visual stimuli presented to the left of a central fixation point can be projected directly to the right hemisphere and visual stimuli presented to the right of a central fixation point can be projected directly to the left hemisphere. Numerous studies usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 69 publications
1
23
1
Order By: Relevance
“…Jordan et al (2000Jordan et al ( , p. 1204 concluded that, "The absence of even a slight word-nonword effect for LVF stimuli in our study suggests that words presented briefly to the right hemisphere were unable to make effective contact with any higherorder representations (i.e., for words or letter groups)." A similar insensitivity of the LVF to the normal superiority of words over unpronounceable nonwords can be discerned in the results of Jordan et al (2003) and Jordan et al (2008). In contrast to this evidence that LVF words may fail to engage lexical representations during the performance of the Reicher-Wheeler task, numerous studies involving naming or lexical decision have found lexical influences on the processing of LVF words.…”
Section: Re-considering the Usefulness Of The Reicher-wheeler Task Inmentioning
confidence: 63%
See 1 more Smart Citation
“…Jordan et al (2000Jordan et al ( , p. 1204 concluded that, "The absence of even a slight word-nonword effect for LVF stimuli in our study suggests that words presented briefly to the right hemisphere were unable to make effective contact with any higherorder representations (i.e., for words or letter groups)." A similar insensitivity of the LVF to the normal superiority of words over unpronounceable nonwords can be discerned in the results of Jordan et al (2003) and Jordan et al (2008). In contrast to this evidence that LVF words may fail to engage lexical representations during the performance of the Reicher-Wheeler task, numerous studies involving naming or lexical decision have found lexical influences on the processing of LVF words.…”
Section: Re-considering the Usefulness Of The Reicher-wheeler Task Inmentioning
confidence: 63%
“…Most of those tasks have then been borrowed by researchers interested in the word recognition capabilities of the two cerebral hemispheres (see Banich, 2004;Ellis, 2004). Jordan and colleagues have championed the use of the Reicher-Wheeler task in hemispheric research, including split-fovea research (e.g., Jordan, Patching, & Milner, 2000;Jordan, Patching, & Thomas, 2003;Jordan, Paterson, & Kurtev, 2009;Jordan, Paterson, & Stachurski, 2008).…”
Section: Re-considering the Usefulness Of The Reicher-wheeler Task Inmentioning
confidence: 99%
“…2, 3.5, 4.9, 6.7, 8.7, 11.1, and 13.7 cpd). Moreover, at each of these frequencies, identification accuracy was higher for words than for nonwords, indicating that information at these spatial frequencies produced different patterns of activation for word and nonword targets (e.g., , 1996Johnston & McClelland, 1980;Jordan et al, 2000;Jordan et al, 2003aJordan et al, , 2003bJordan, Redwood, & Patching, 2003;McClelland & Rumelhart, 1981Paap et al, 1982; see also Carr & Pollatsek, 1985). The precise nature and extent of these differences in activation produced by the filtered images of words and nonwords used in this study remains to be determined.…”
Section: Reading Ability and Word And Nonword Perceptionmentioning
confidence: 99%
“…It is well established that letters in briefly exposed stimuli can be identified more accurately in words than in nonwords (the word-nonword effect; Hildebrandt, Caplan, Sokol, & Torreano, 1995;Johnston, 1978;Jordan et al, 2000;Jordan, Patching, & Thomas, 2003a, 2003bJordan, Redwood, & Patching, 2003;Krueger, 1975;McClelland, 1976;McClelland & Johnston, 1977;McClelland & Rumelhart, 1981;Reicher, 1969;Wheeler, 1970), indicating activation of orthographic and lexical processes involved in word perception , 1996Johnston & McClelland, 1980;Jordan et al, 2000;Jordan et al, 2003aJordan et al, , 2003bMcClelland & Rumelhart, 1981Paap, Newsome, McDonald, & Schvaneveldt, 1982). Therefore, if word-nonword effects obtain with filtered stimuli, this would suggest that the spatial frequency information present in filtered word stimuli can activate processes of word perception.…”
mentioning
confidence: 99%
“…However, Smith (1977) has argued that this method does not completely eliminate afterimages for adaptation stimuli of below 3-4 cpd. Moreover, other evidence suggests that instructions alone do not determine the pattern of eye movements actually implemented by participants (e.g., Jordan & Patching, 2006;Jordan, Patching, & Milner, 1998;Jordan, Patching, & Thomas, 2003a, 2003b. Consequently, a better approach is to alter the retinal location of the components of each grating by randomly varying the onscreen characteristics of the stimulus.…”
Section: Avoiding Afterimagesmentioning
confidence: 99%